Evaluation of extracts from used Xpert MTB/RIF cartridges for detection of resistance to second-line anti-tuberculosis drugs in patients with multidrug-resistant tuberculosis in Ethiopia - Tilahun Ketema; Mulualem Tadesse; Zegeye Bonsa; Getu Balay; Wakjira Kebede; Mekidim Mekonnen; Gemeda Abebe (BMC Microbiology)
Abstract Background Early and accurate diagnosis of drug resistance, including resistance to second-line anti-tuberculosis (TB) drugs, is crucial for the effective control and management of pre-extensively drug-resistant TB (pre-XDR-TB) and extensively drug-resistant TB (XDR-TB). The Xpert MTB/XDR assay is the WHO recommended method for detecting resistance to isoniazid and second-line anti-TB drugs when rifampicin resistance is detected. Currently, the Xpert MTB/XDR assay is not yet implemented in Ethiopia, thus the MTBDRsl assay continues to be used. However, the MTBDRsl assay requires additional patient visits and specimen collection, which can lead to delays in diagnosis and treatment initiation. Objective This study aimed to evaluate the feasibility of using extracts from used Xpert MTB/RIF cartridges for detecting resistance to second-line anti-TB drugs by MTBDRsl assay in patients with rifampicin resistant-TB (RR-TB) in Eastern and Western Oromia, Ethiopia. Methods A cross-sectional diagnostic evaluation study was conducted from June 2020 to May 2021 at two TB Referral Laboratories in Eastern and Western Oromia, Ethiopia. Sputum samples from RR-TB patients were split, with one aliquot being subjected for Xpert testing and the other being cultured on Lowenstein-Jensen media. DNA extracted from the used Xpert cartridges was amplified by PCR and tested by MTBDRsl assay, and the results were compared to those obtained from culture isolates. To establish the detection limits, the MTBDRsl assay was performed on cartridge extracts (CEs) from a series of dilutions of drug-susceptible and multidrug-resistant TB strains. Results The MTBDRsl on CEs from dilutions at ≥ 102 CFU/mL (CT ≤ 22) accurately identified susceptibility and resistance patterns for fluoroquinolones (FQL) and second-line injectable drugs (SLIDs). The MTBDRsl on rifampicin-resistant CEs from sputum samples (n = 40) yielded 100% interpretable results for FQL and 90% (4 indeterminate) interpretable results for SLIDs. All interpretable CE results showed complete agreement with the MTBDRsl results from the culture isolates. Conclusion This study demonstrated the feasibility of using extracts from used Xpert MTB/RIF cartridges for detecting resistance to second-line anti-TB drugs using the MTBDRsl assay. This approach could mitigate the need for additional specimen collection and allow for earlier treatment initiation, potentially improving patient outcomes and reducing the transmission of drug-resistant TB strains.